2008
DOI: 10.1007/s00227-008-1060-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of stable isotopes and mercury concentrations to describe seabird foraging ecology in tropical environments

Abstract: International audienceNitrogen (δ15N) and carbon (δ13C) stable isotopes and contaminants, such as mercury, have been widely used to characterise foraging ecology of temperate and polar seabirds. In this study, for the first time, we used isotopic signatures and mercury levels of feathers and blood of eight tropical seabird species, that forage in a range-gradient between inshore and offshore areas, to describe the foraging habits of a large tropical seabird community (from two neighbouring islands of the Seych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 49 publications
7
25
0
Order By: Relevance
“…Our study shows, for instance, that average Hg concentration was much higher in French Guiana compared to another tropical seabird community in Seychelles archipelago (Catry et al, 2008). Further, despite in Catry et al (2008) Hg analyses were performed using whole blood, which reflects relatively similar concentrations than that of red blood cells, Hg concentrations in the Brown noddy were much lower than those of French Guiana (Catry et al, 2008). Similar Hg concentrations have been previously associated with deleterious effects (Costantini et al, 2014;Tartu et al, 2016) with consequences at the population level such as reduction of breeding, hatching and fledging success, and population decline (Goutte et al, 2014a(Goutte et al, , 2014b.…”
Section: Trace Elements and Pops Toxicitymentioning
confidence: 49%
See 3 more Smart Citations
“…Our study shows, for instance, that average Hg concentration was much higher in French Guiana compared to another tropical seabird community in Seychelles archipelago (Catry et al, 2008). Further, despite in Catry et al (2008) Hg analyses were performed using whole blood, which reflects relatively similar concentrations than that of red blood cells, Hg concentrations in the Brown noddy were much lower than those of French Guiana (Catry et al, 2008). Similar Hg concentrations have been previously associated with deleterious effects (Costantini et al, 2014;Tartu et al, 2016) with consequences at the population level such as reduction of breeding, hatching and fledging success, and population decline (Goutte et al, 2014a(Goutte et al, , 2014b.…”
Section: Trace Elements and Pops Toxicitymentioning
confidence: 49%
“…However, they are similar to highcontaminated seabirds in other areas whether from temperate, subpolar, or polar regions (Supplementary Figure S2). Our study shows, for instance, that average Hg concentration was much higher in French Guiana compared to another tropical seabird community in Seychelles archipelago (Catry et al, 2008). Further, despite in Catry et al (2008) Hg analyses were performed using whole blood, which reflects relatively similar concentrations than that of red blood cells, Hg concentrations in the Brown noddy were much lower than those of French Guiana (Catry et al, 2008).…”
Section: Trace Elements and Pops Toxicitymentioning
confidence: 53%
See 2 more Smart Citations
“…In one of the few studies on pollutants in marine birds from the western Indian Ocean, Catry et al (2008) detected no differences in trophic feeding ecology based on stable isotopes in feathers or blood, nor any differences in mercury levels between the Sooty Tern and Common Noddy, despite the differences (though overlapping) in prey items and foraging ecology. On the other hand, Ramos and Tavares (2010) found that lower levels of mercury in feathers of inshore foraging species from the Seychelles compared with offshore feeding species such as the Sooty Tern.…”
Section: Species Comparisonsmentioning
confidence: 87%